Environmental graphics in strengthening the branding of Jepara carving city - Setiawan, Agus; Khamadi, Khamadi (Gelar: Jurnal Seni Budaya, 2024)
Various decorative patterns from carving art have become part of Jepara's local culture and wisdom. Cultural identity and traditions are depicted in Jepara ornaments as socio-spatial constructions. By making carved motifs and placing them in various corners of the city, Jepara ornaments become the identity of the city. This research aims to explain the existence of Jepara ornaments as a form of local wisdom of the Jepara people. Creating ornaments to strengthen the identity landmarks of Jepara Carving City and creating a graphic environment based on ornaments to strengthen the city's branding. This research uses descriptive qualitative methods to explain Jepara carving art and a branding approach for environmental graphic analysis. This research produces an environmental graphic design model that uses a system of signs, advertising, typography and landmark ornaments to build the face of Jepara as a carving city.